Development of lectin powered lateral flow immunoassay for detection of CA 125 glycovariants in urine - Kallio, Sami (My University, 2022)
Epithelial ovarian cancer (EOC), covering over 90 % of all ovarian cancers, is the eighth most common malignancy in women. Due to its symptom free nature, EOC is typically diagnosed at a late stage, with 5-year survival rate of only 30 %. With more timely diagnosis the survival rate increases to 84 %, highlighting the crucial need for more sensitive diagnostic methods. Cancer antigen 125 (CA 125) is a large transmembrane glycoprotein and part of the mucin protein family. The levels of CA 125 in serum have traditionally been used for EOC diagnostics, but it has limitations regarding its sensitivity and specificity. CA 125 is expressed in many other malignant and non-malignant conditions hindering specificity and its expression in EOC varies widely between the stage and the type of tumour limiting its sensitivity. The aim of this thesis was to develop a lateral flow (LF) assay able to detect the cancer specific glycoform of CA 125 from urine samples. A point-of-care assay would enable non-invasive method for monitoring treatment progression and cancer relapse. The distinction between malignant and non-malignant CA 125 is based on the aberrant glycosylation inherent in cancer derived biomarkers. The LF assay uses anti-CA 125 monoclonal antibodies as capture reagents and Eu+3-doped nanoparticles conjugated either with macrophage galactose-type lectin or Wisteria floribunda agglutinin (WFA) lectins as tracer element. The developed LF assay utilizing WFA nanoparticles reached a limit of detection of 7.6 U/ml, which is below the clinically relevant 10 U/ml of CA 125 in urine. Two key findings enabling this assay were the low pH 6.1 assay buffer and the pre-treatment of urine sample by heating to combat the matrix effect caused by urine. The LF assay needs further development especially a functioning control line and testing with clinical samples must be performed in the future.
Keywords: lateral flow immunoassay, epithelial ovarian cancer, CA 125, MUC 16, glycovariant, lectins, WFA